El videojuego histórico como memoria literal y memoria ejemplar - Venegas Ramos, Alberto (Historiografías, 2019)
The objective of this work is to examine the clues contained in the video game of historical theme. We shall start with the distinction, by Tzvetan Todorov, between literal and exemplary memories by studying two historical titles, Red Dead Redemption 2 (Rockstar Games, 2018) and This War of Mine (11-bit studios, 2014), to illustrate each type of memory. On this basis we will take for its examination three aspects of each of them, the authors’ intention, and the messages and the images contained in the video game. All this, together with the historiographical context, will offer us the necessary information to approach, in more a general context, to the causes and consequences of memories in the mass media.